Tomes! Enhancing Community and Embracing Diversity Through Book Arts - Beene, Stephanie J.; González, Lauri M.; Schadl, Suzanne M. (Radical Teacher, 2018)
This article highlights important connections between the spoken word, handmade paper, cultural memory and natural sustenance -- in books and in artworks. Two projects were brought together for an exhibition, which serves as an innovative response to the call for multiculturalism, inclusion, and equity at an educational institution in one of the most multilingual and multicultural states in the U.S. Any organization which mounts an exhibition runs the risk of assuming they know what visitors want to see, or ought to see, and how they might choose to experience the works displayed. This exhibit is an attempt to subvert that tendency and extend the continuum of authority, offering visitors multiple modes for leaving their mark on the exhibit. Preliminary comments demonstrate how performative and tactile object-based inquiry leads to transformative learning. How do communities interact with and describe materials whose intent is to push what comfortably translates between English and Spanish? How can we collaborate to provide better access to collections that represent their families, communities, or traditions? What sorts of differences are observed between the ways people handle and describe unique objects if they are not instructed first? The exhibit continues to evolve according to community feedback. This article discusses one approach to collaboration as an effective tool for breaking down barriers to traditional authority and hierarchies.